UJI EFEKTIVITAS DAUN PANDAN WANGI (PANDANUS AMARYLLIFOLIUS ROXB.) SEBAGAI ANTIBAKTERI TERHADAP SALMONELLA TYPHI - Priska Nancy Claudia Bali; Ahmad Raif; Setia Budi Tarigan (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2019)
Pandanus amaryllifolius roxb leaves commonly used as food dditives which contain various compound groups namely alkaloid, saponins, flavonoids and tannins that have a role in antibacterial activity. This research is indicated to support the success of antibacterial in fragrant pandanus leaf plants against Salmonella typhi, one of the pathogenic bacteria. The antibacterial effectiveness test of ethanol-ethyl acetate extract (1: 1) of pandanus leaves which evaluated by the Kirby-bauer method and making the extract concentrations of 25%, 50%, 75%, 100%. The results showed that pandanus leaves extract had antibacterial effectiveness against Salmonella typhi with an average inhibition zone diameter of 11.6 mm; 14 mm; 14.3 mm; 15.3 mm; positive controls (Ciprofloxacin) 27 mm; and negative controls (aquadest) didn’t produce the inhibition zone of Salmonella typhi.